THE DEVELOPMENT OF TEACHER CHARACTERS BASIS OF TASAWUF - Afif Muhammad; Dian Dian (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2015)
This paper is based on the reality of education system in Indonesia which is still far from expectations, especially in shaping the character of teachers and students. In various cases, it is still found sexual abuse committed by teachers and students as well as the number of users and drug addicts among students. The purpose of this research is to find the root causes of problems and workable solutions to build the characters of teachers and students in the education system in Indonesia. The method used in this research is content analysis method. Data were analyzed using the approach of Sufism. This approach has three main methods which are, then, implemented in learning activities and interaction between teachers and students. The methods include takhally, tahally and tajally. Through takhally method, teachers and students are invited to have candor in doing to avoid the properties 'ujub, riya and disinterested. Moreover, tahally method becomes embedded properties of the pleasure meanwhil tawadhdhu‟ is act solely for Allah. Thus, these methods bear the loyalty of teachers, decrease negative rivalry and increase work productivity.